THE IMPORTANCE OF INTERNATIONAL STANDARDS IN ENHANCING THE TRANSPARENCY OF FINANCIAL REPORTING IN PUBLIC HIGHER EDUCATION INSTITUTIONS (E Global Congress, 2026)
Transparency in financial reporting is a critical factor in ensuring accountability and efficient resource allocation in public higher education institutions (HEIs). This study examines the role of international financial reporting standards in improving transparency, comparability, and reliability of financial information in HEIs. The findings indicate that the adoption of standardized reporting frameworks enhances the clarity of revenue structures, improves monitoring of public funds, and supports evidence-based decision-making. Empirical evidence shows that public HEIs receive a significant share of their revenues from state funding, while alternative sources such as student fees and third-party funding remain relatively limited [1]. At the same time, international analyses highlight the importance of transparent cost allocation and diversified funding models for ensuring financial sustainability [2]. The study concludes that the implementation of international standards strengthens financial discipline, increases institutional accountability, and reduces information asymmetry in the higher education sector.